Venezuela’s communication dynamics in rejection of humanitarian assistance from United States of America - Kuma Jaya (International Journal of Communication and Society, 2019)
This paper aims to find out how the communication dynamics by the Venezuelan government when dealing with humanitarian assistance provided by the international community, especially the United States. Venezuela is colaps, the international community including the United States wants to provide assistance to them, but the president of Venezuela, Maduro, refuses the aid. This research method uses interpretative case study methods. According to Casel and Simon, qualitative methods are social science research methods that attempt to accurately describe and interpret the meaning of symptoms that occur in a social context The United States had to continue and improve diplomatic leadership and assistance in response to the Venezuelan.